Schizophrenia and Category-Selectivity in the Brain: Normal for Faces but Abnormal for Houses - Kronbichler, Lisa; Stelzig-Schöler, Renate; Pearce, Brandy-Gale; Tschernegg, Melanie; Said-Yürekli, Sarah; Reich, Luise Antonia; Weber, Stefanie; Aichhorn, Wolfgang; Kronbichler, Martin (Frontiers in Psychiatry, 2018)
Face processing is regularly found to be impaired in schizophrenia (SZ), thus suggesting that social malfunctioning might be caused by dysfunctional face processing. Most studies focused on emotional face processes, whereas non-emotional face processing received less attention. While current reports on abnormal face processing in SZ are mixed, examinations of non-emotional face processing compared to adequate control stimuli may clarify whether SZ is characterised by a face processing deficit. Patients with SZ (n=28) and healthy controls (n=30) engaged in an fMRI scan where images of non-emotional faces and houses were presented. A simple inverted-picture detection task warranted the participants’ attention. Regions of Interest (ROI) analyses were conducted on face-sensitive regions including the fusiform face area, the occipital face area and the superior temporal sulcus. Scene-sensitivity was assessed in the parahippocampal place area (PPA) and served as control condition. Patients did not show aberrant face-related neural processes in face-sensitive regions. This finding was also evident when analyses were done on individually defined ROIs or on in-house-localizer ROIs. Patients revealed a decreased specificity towards house stimuli as reflected in decreased neural response towards houses in the PPA. Again, this result was supported by supplementary analyses. Neural activation towards neutral faces was not found to be impaired in SZ, therefore speaking against an overall face-processing deficit. Aberrant activation in scene-sensitive PPA is also found in assessments of memory processes in SZ. It is up to future studies to show how impairments in PPA relate to functional outcome in SZ.